Reforming pensions in developing and transition countries - Hujo, Katja; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book moves beyond technical studies of pension systems by addressing the political economy of pension reform in different contexts. It provides insights into key issues related to pension policy and its developmental implications, drawing on selected country studies in Africa, Asia, Eastern Europe, the Middle East, and Latin America.
Keywords: Science